PENGARUH HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA COFFEE SHOP SODARE KOPI TEBET JAKARTA SELATAN - M Satyono Rama Dani; Novia Susanti (Journal of Research and Publication Innovation, 2025)
The purpose of this study was to determine the effect of price and service quality variables on customer satisfaction at Sodare Kopi Coffee Shop, Tebet, South Jakarta, partially and simultaneously. The method used is quantitative. The sampling technique was 98 respondents. Data analysis used Validity test, reliability test, classical assumption test, regression analysis, correlation coefficient analysis, determinant coefficient analysis and hypothesis test. The results of this study are that price has a positive and significant effect on customer satisfaction with the regression equation Y = 14.797 + 0.396 X1. Hypothesis testing obtained a t-count value> t-table or (6.055> 1.985) then Price (X1) has a positive and significant effect on the Customer Satisfaction variable (Y) which can be concluded that Ha₁ is accepted and H₀₁ is rejected. Service quality has a positive and significant effect on customer satisfaction with the regression equation Y = 7.711 + 0.496 X2. Hypothesis test obtained t-count value > t-table or (9.180 > 1.985) then Service Quality (X2) has a positive and significant influence on Customer Satisfaction variable (Y) which can be concluded that Ha₂ is accepted and H₀₂ is rejected. Price and service quality have a positive and significant influence on customer satisfaction with the regression equation Y = 7.670 + 0.023 X1 + 0.479 X2 +e. Hypothesis test obtained Fcount value> Ftable or (41.768> 3.092). This is also reinforced by ρ values < Sig 0.05 or (0.000 < 0.05). Thus H₀₃ is rejected and Ha₃ is accepted. This shows that there is a significant influence simultaneously (together) between Price and Service Quality on Customer Satisfaction.